SIGNIFICANT CORRELATION BETWEEN LACK OF VITAMIN D LEVELS 25 OH IN PREGNANT WOMEN WITH LOW BIRTH WEIGHT - Diah Lestari; Dwi Rahmawati; Yosanti Elsa (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2023)
Pregnant women who lack in vitamin D will increase the risk of fetal growth and development, one of which is births with low birth weight (LBW). Vitamin D functions for calcium absorption up to 60% during pregnancy for fetal bone growth. This study aims to determine the correlation between vitamin D levels in pregnant women and low birth weight babies at RSAB Harapan Kita. The research method uses a cross-sectional design. The population was pregnant women who checked levels of Vitamin D (Vit D 25 (OH)) in the first trimester and third trimester with sample size of 80. The data analysis used is the Chi-Square test. Examination of vitamin D levels with the ELISA method. The results showed that the average level of vitamin D content was abnormal (Insufficient and Deficient) 73.8%, and normal vitamin D content (Sufficient) 26.2%. The mean of extremely low birth weight (ELBW) was 13.8%, very low birth weight (VLBW) was 26.2% and low birth weight (LBW) was 60.0%. There was a significant correlation between vitamin D levels in pregnant women and low birth weight (Sig = 0.025), (p < 0.05). Conclusions vitamin D intake in pregnant women is needed for fetal development to reduce the risk of low birth weight (LBW).